A new chemosensor for Ga3+ detection by fluorescent nitrogen-doped graphitic carbon dots1. Issue 17 (27th February 2015) - Wang, Hao; Wang, Yun; Guo, Jun; Su, Ying; Sun, Cheng; Zhao, Jie; Luo, Hongmei; Dai, Xiao; Zou, Guifu
<x xml:space="preserve">Abstract</x> Nitrogen-doped graphitic carbon dots as chemosensors show a sensitive response (209 nM) to Ga3+ in range of 0–20 μM.